O stylistycznym zróżnicowaniu dawnej leksyki – na przykładzie oficjalnych i potocznych nazw dziecka nieślubnego - Woźniak, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The author attempts to determine stylistically three old terms for extramarital child: wyleganiec, pokrzywnik and bękart. These words have been up to now classified as colloquial and expressive, with negative undertone. They appear separately in the Old Polish and 16th century texts and are of different character. An abusive term pokrzywnik is recorded only in relation to defamation cases. Official terms wyleganiec and bękart are present in old legal texts, biblical translations and dictionaries. This regularity shows the beginning of stylistic differentiation in the Old Polish lexicon, however the author is aware that the difference between colloquial and formal terms in the past was not necessarily so sharp as it is today and we cannot attribute present meaning to the past lexicon.